1999
DOI: 10.1007/bf02358170
|View full text |Cite
|
Sign up to set email alerts
|

The use of image analysis to study developmental variation in micropropagated potato (Solanum tuberosum L.) plants

Abstract: SummaryPotato leaf morphology changes during plant development with the phase shift from vegetative growth to flowering. Image analysis can detect differences in leaf morphology and has been used here to distinguish differences in leaf morphology between potato crops derived from seed tubers and minitubers and between crops derived from different micropropagation protocols. Further, leaf shape parameters can be used to determine the relative maturity of crops. This finding is of economic importance since diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…the lower concentrations tested had no effect on yield parameters (table 1, Figure 1). Some authors showed that the quality of in vitro plants has influenced acclimatization and subsequent development of plantlets in the field (Cassells et al 1999. a good physiological condition of in vitro plants is a guarantee of the later successful seed production process in greenhouse.…”
Section: Resultsmentioning
confidence: 99%
“…the lower concentrations tested had no effect on yield parameters (table 1, Figure 1). Some authors showed that the quality of in vitro plants has influenced acclimatization and subsequent development of plantlets in the field (Cassells et al 1999. a good physiological condition of in vitro plants is a guarantee of the later successful seed production process in greenhouse.…”
Section: Resultsmentioning
confidence: 99%
“…Plant quality in vitro has been shown to influence subsequent development of plantlets at acclimatisation and in the field (Cassells et al 1999;Kowalski et al 1999aKowalski et al , b, 2003. Apparently, a favourable physiological condition can be established in the in vitro phase, which is then carried through to the later stages of the seed production process in greenhouse and field.…”
Section: Discussionmentioning
confidence: 98%
“…It's made from chitin shells of shrimp, crabs and other crustaceans with an alkaline substance and is also found in both fungal and insect cell walls W alker-Simmons et al (1983). It's also the antifungal agent against plant disease resistance and nontoxic effect on the environment (Vander et al 1998;Benhamou et al 1994;El-Ghaouth et al 1994, Cassells et al 1999Roby et al 1987 andTiuterev et al 1996). Chitosan has so many properties like growth stimulator, antimicrobial properties, plant disease resistance, biodegradability, biocompatible for the environment, etc Uthairatanakij et al (2007).…”
mentioning
confidence: 99%